2022
DOI: 10.1002/jbio.202200079
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of histopathological response to neoadjuvant therapy in rectal cancer using slide‐free, stain‐free multimodal multiphoton microscopy

Abstract: Neoadjuvant therapy has become a standard treatment for patients with locally advanced rectal cancer to achieve better prognostic outcomes. The response to treatment has been shown to correlate closely with the prognosis. However, current evaluation systems only provide coarse assessment on limited information, due to the lack of accurate and reproducible approach for quantitation of different types of responses. In this study, a novel stain‐free, slide‐free multimodal multiphoton microscopy imaging technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Therefore, MPM can provide high-contrast images of cells as well as extracellular mesenchyme [ 18 , 19 ]. This capability helps basic and clinical researchers acquire detailed microstructural information of biological tissues [ 20 ], and previous studies demonstrated that MPM imaging could offer significant advantages in cancer detection, disease process research and the qualitative and quantitative analysis of collagen fibers within tumor microenvironment [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, MPM can provide high-contrast images of cells as well as extracellular mesenchyme [ 18 , 19 ]. This capability helps basic and clinical researchers acquire detailed microstructural information of biological tissues [ 20 ], and previous studies demonstrated that MPM imaging could offer significant advantages in cancer detection, disease process research and the qualitative and quantitative analysis of collagen fibers within tumor microenvironment [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%